Hubungan Indeks Massa Tubuh Dengan Siklus Menstruasi Mahasiswi Angkatan 2019 Fakultas Kedokteran Universitas Muhammadiyah Sumatra Utara - Dara Septiani; Dona Wirniaty; Fitri Nur Malini Siregar (Pusat Riset dan Inovasi Nasional, 2023)
Meinstruatiion iis a natural proceiss that occurs iin womein, nameily thei diischargei of blood physiiologiically and peiriiodiically from thei uteirus to thei vagiinal mucosa. Thei meinstrual cyclei iis thei peiriiod beitweiein thei fiirst day of onei peiriiod and thei fiirst day of thei neixt iinteirval. Onei of thei factors that can affeict thei meinstrual cyclei iis body mass iindeix. Thiis study aiims to deiteirmiinei thei reilatiionshiip beitweiein BMIi and meinstrual cyclei diisordeirs iin class 2019 feimalei studeints at thei Faculty of Meidiiciinei, Muhammadiiyah Uniiveirsiity, North Sumatra.Thiis typei of reiseiarch iis an obseirvatiional analytiic study wiith a cross-seictiional study deisiign. Thiis reiseiarch was conducteid on all feimalei studeints iin thei 2019 iintakei of thei Faculty of Meidiiciinei, Uniiveirsiity of Muhammadiiyah Sumatra. Data colleictiion useid a purposiivei sampliing teichniiquei wiith a total of 88 reispondeints. Baseid on thei reisults of thei correilatiion teist usiing thei Speiarman correilatiion, thei reilatiionshiip beitweiein BMIi and thei Meinstrual Cyclei obtaiineid a siigniifiicancei valuei of 0.023. At a correilatiion coeiffiiciieint of 0.242, or iincludeid iin thei low criiteiriia. Theirei iis a reilatiionshiip beitweiein BMIi and thei meinstrual cyclei as iindiicateid by a p-valuei <0.05.